Analysis of nutrition and nutritional status of haemodialysis patients - Anna Bogacka; Anna Sobczak-Czynsz; Elżbieta Kucharska; Małgorzata Madaj; Katarzyna Stucka (National Institute of Public Health - National Institute of Hygiene, 2018)
Background. Chronic kidney disease (CKD) is a common disease of civilization where nutrition is part of the treatment. Diet therapy is difficult as it is necessary to control the intake of: energy, protein and minerals - Na, K, Ca and P in the daily food rations (DFR). Objective. The aim of the study was to assess the nutritional status and diets of haemodialysis (HD) patients. Material and methods. The study involved 141 haemodialysis patients, at the average age of 65.9. The patients were divided into groups taking into consideration their sex and diagnosis for diabetes. The information on the diets were collected using a 7-day dietary recall. In the DFRs the amount of energy and 22 nutrients were calculated. Obtained results were compared with requirements for HD patients. Results. Appropriate nutritional status (measured with BMI) was reported for majority of women (70.6%) and almost half of men, however, excessive weight was recognized in every third female patient and more than half male patients, and type I obesity was noted in 7.8% of men. The analysis of the results showed that diets of all examined patients were deficient in energy and protein (except women with diabetes), whereas the consumption of fat was appropriate in both groups of women. The recommendations with respect to the amount of cholesterol were met but dietary fibre was too low. Intake of vitamins B1, D, C, folates and Ca and Mg was lower and intake of vitamin B12 was higher than recommended. Conclusions. Assessment of the coverage of the demand on nutrients in HD patients should not be based on the analysis of their nutritional status (BMI) only but also on the analysis of diets, especially in case of diabetes.